Polsko-mołdawski konflikt handlowy w latach 1780–1785 a polityka wewnętrzna Stanisława Augusta Poniatowskiego - Filipczak, Witold (Władza i polityka w czasach nowożytnych. Dyplomacja i sprawy wewnętrzne, 2020)
The conflict over trade between Poland and Moldavia in the 80s of the 18th century has already elicited interest of historians from Poland, Romania and Moldova. The contributions of Jan Reychman, Veniamin Ciobanu and Valentin Arapu are particularly relevant but they do not exhaust the analyzed topic. The time-frame of the article is 1780–1785 although the origin of the conflict dates back to 1778 when Constantin Moruzi forbade the import of Polish vodka to Moldavia. The year 1785 accepted as the final element in the time-frame does to mean that the conflict came to an end then. After Antoni Dzieduszycki had left Istanbul in 1780, the Polish affairs were taken over by Stanisław Pichelstein, whose official role was that of translator (dragoman) and Head of School of Oriental Languages. The article ends with the accession to the throne of Alexandru Mavrocordat II, who succeeded Alexandru Mavrocordat I; the ensuing response of the Polish political elite to this event is also analyzed. The sources that constitute the basis for the analysis come from The Central Archives of Historical Records in Warsaw, and they include the correspondence of Pichelstein with Stanisław August’s cabinet and Department of Foreign Affairs of the Permanent Council. Another important source that has not been used so far is Stanisław August’s domestic correspondence from the Princes Czartoryski Library in Cracow. It shows how the Polish court tried to make use of the contacts established with hospodars by the high-ranking officials from the voivodeships bordering on Moldavia (i.e. the voivodeships of Braclaw and Podolia) who made demands on Jassy. On behalf of the nobility in their voivodeships, the aforementioned officials demanded that restrictions on the vodka trade should be lifted. This was done in strict agreement with the recommendations from Warsaw.